Stroke incidence between stenting and endarterectomy for asymptomatic carotid artery stenosis. (July 2022) - Rahim, Ahmed Abdel; Thabet, Mahmoud Ahmed; Galal, Ali Mahmoud; Hammoda, Mohamed Ibrahim; Mittapalli, Devender
Abstract: A best evidence topic has been constructed using a described protocol. The three-part question addressed was: In patients with significant asymptomatic carotid artery stenosis (ACAS), Does Carotid artery stenting (CAS) has a peri-procedural lower Stroke rate, As compared to Carotid endarterectomy (CEA)? The outcomes assessed were the stroke rate in the two management modalities. The best evidence showed no statistically significant difference between CAS and CEA regarding the peri-procedural and the long-term non-procedural stroke incidence. However, in high-risk patients, CAS may be a better option. Highlights: Carotid artery stenting and carotid endarterectomy have the same peri-procedural and post-procedural stroke incidence rates in treatment of carotid artery stenosis. In high risk patients, Carotid artery stenting is a better option than carotid endarterectomy.